Fishermen's Adaptation Strategy to the Impact of Climate Change in Lamanggau Village, Tomia Sub-district, Wakatobi Regency - Alan Suyitno; Saediman, Saediman; Munirwan Zani (International Journal of Technology and Education Research, 2024)
This study aims to (1) determine the types of livelihoods of fishermen in Lamanggau Village, Tomia District, Wakatobi Regency, (2) determine the perception of fishermen towards climate change and its impacts in Lamanggau Village, Tomia District, Wakatobi Regency, and (3) determine the adaptation strategies of fishermen to the impacts of climate change in an effort to maintain the sustainability of their livelihoods in Lamanggau Village, Tomia District, Wakatobi Regency. The population in this study was the fishermen in Lamanggau Village, 150 people. The determination of the research sample was carried out using the Slovin formula, so that 35 respondents were obtained. The research analysis used qualitative descriptive analysis and a Likert scale. The results of the study showed that the types of livelihoods of fishermen in Lamanggau Village were trolling, octopus fishing, squid fishing, drag nets, and gill nets. Then the perception of fishermen towards climate change and its impacts in Lamanggau Village is still very bad. And the fishermen's adaptation strategy to the impacts of climate change in an effort to maintain the sustainability of community livelihoods is carried out in a good way, whether in the form of using environmentally friendly fishing gear, changing the location or fishing to anticipate climate change, diversifying livelihoods outside the fishing profession and participating in training on sustainable fishing techniques